BIO EFFICACY OF SPIROMESIFEN 240 SC AGAINST MITE PESTS IN CUCUMBER - RAGHAVENDRA YALIGAR; BASAVARAJ KALMATH; MAHANTESH KAPASI (The Bioscan, 2015)
Field trial was conducted at Agricultural Research Station, Kawadimattii, during kharif 2012-13 and 2013-14 to evaluate the efficacy of Spiromesifen 240 SC at different dosage for the management of mite pests on cucumber. The standard acaricides viz., Dicofol, Propergite and Fenazaquin were used for comparison. Overall the field trials revealed that, Spiromesifen 240SC @ 120 g a.i/ha emerged as a best and optimum dose as it registered lowest number of mites (1.25/leaf) at 10 days after first spray and recorded highest yield of 22.61 q/ha. Whereas, Dicofol, Propergite and Fenzaquin recorded 4.46, 2.01 and 2.27 mite per leafat 10 days after first spray. The foregoing studies indicated that all the acaricides tested for mite pest were proved superiorover control and the performance of Spiromesifen 240 SC @ 120 g a.i/ha was superior to other dosages in terms of suppression of mite population and harnessing higher yield.